Extent of Induced Variation in M2 Progenies of Coriander - Swami, M L; Ramkrishna, K; Sharma, R K (Annals of Arid Zone, 2016)
A study was conducted during rabi season of’ 1996-97 to evaluate extent of induced variation for various quantitative characters in M;2 progenies of coriander variety UD-436. These M2 progenies were originally obtained by treating the seeds with 15, 20, 25 kR doses of gamma irradiation with or without sodium azide (1 mM) and hydroxylamine (I %) and following selfing of M, progeny. The inter-progeny variance was highly significant, whereas the intra-progeny variance was non-significant for all the traits studied. Progenies differing significantly from the control on positive and negative directions were more frequent for all the traits except grain yield per plant and IDO-grain weight. Based on mean and coefficient of variation, two progenies, namely 43 and 56, may be advanced to M3 generation to obtain even better segregants.